Analisis efisiensi pengelolaan Dana Alokasi Umum Kabupaten atau Kota di Pulau Kalimantan - Devi Utami Rika Safitri; Widarjono, Agus (Jurusan Ilmu Ekonomi, Fakultas Bisnis dan Ekonomika, Universitas Islam Indonesia, 2023)
Purpose – This study aims to analyze the efficiency levels in managing the General Allocation Fund in regencies and cities for the purpose of equalizing financial capacity in the endeavor of human development in Kalimantan Island.Methods – Two testing models, namely Data Envelopment Analysis (DEA) and Panel Data Regression Model, were employed on 56 regencies and cities in Kalimantan Island with the primary variable being the General Allocation Fund absorption reports from 2018 to 2022.Findings – The majority of regencies and cities in Kalimantan Island have managed the General Allocation Fund with relatively high-efficiency levels, ranging from 0.86 to 0.98. Regression analysis indicates that Gross Regional Domestic Product has a significant influence on the regression outcome. On the other hand, Regional Original Revenue exerts a less significant effect, while the Poverty Percentage holds a significant negative impact. The panel test results demonstrate that the Fixed Effect (FE) approach is the most suitable model with a remarkably high R-squared value of 0.990803.Implication – In general, regencies and cities in Kalimantan Island have managed the General Allocation Fun efficiently. However, in a policy context, continuous monitoring and evaluation are necessary to ensure optimal utilization of the DAU in supporting regional development.Originality – This study contributes to the evaluation and formulation of optimum values in managing the General Allocation Fund for regencies and cities in Kalimantan Island. AbstrakTujuan – Menganalisa tingkat efisiensi pengelolaan Dana Alokasi Umum (DAU) Kabupaten/Kota terhadap Pemerataan Kemampuan Keuangan dalam upaya pembangunan manusia di Pulau KalimantanMetode – Terdapat dua model pengujian yakni Data Envelopment Analysis (DEA) dan Model Regresi Data Panel pada 56 Kabupaten/Kota di Pulau Kalimantan dengan variabel utama laporan penyerapan Dana Alokasi Umum (DAU) tahun 2018 sampai 2022.Temuan – Sebagian besar kabupaten/kota di Pulau Kalimantan telah mengelola Dana Alokasi Umum (DAU) dengan tingkat efisiensi yang relatif tinggi, berkisar antara 0.86 hingga 0.98. Analisis regresi menunjukkan bahwa PDRB pengaruh signifikan terhadap hasil regresi. Sedangkan, PAD memiliki pengaruh yang kurang signifikan, sementara Persentase Kemiskinan memiliki pengaruh negatif yang signifikan. Hasil uji panel menunjukkan bahwa pendekatan Fixed Effect (FE) adalah model terbaik dengan nilai R-squared yang sangat tinggi (0.990803). Implikasi – Secara garis besar kabupaten/kota di Pulau Kalimantan telah mengelola DAU secara efisien. Namun, dalam konteks kebijakan, perlu dilakukan pemantauan dan evaluasi untuk memastikan penggunaan DAU yang optimal dalam mendukung pembangunan daerah. Orisinalitas – Penelitian ini berkontribusi dalam mengevaluasi dan memformulasikan nilai optimum dalam pengelolaan Dana Alokasi Umum (DAU) untuk Kabupaten/Kota di Pulau Kalimantan.